Improvement of mRNA Delivery Efficiency to a T Cell Line by Modulating PEG-Lipid Content and Phospholipid Components of Lipid Nanoparticles - Hiroki Tanaka; Ryo Miyama; Yu Sakurai; Shinya Tamagawa; Yuta Nakai; Kota Tange; Hiroki Yoshioka; Hidetaka Akita (MDPI AG, 2021)
(1) Background: T cells are important target cells, since they exert direct cytotoxic effects on infected/malignant cells, and affect the regulatory functions of other immune cells in a target antigen-specific manner. One of the current approaches for modifying the function of T cells is gene transfection by viral vectors. However, the insertion of the exogenous DNA molecules into the genome is attended by the risk of mutagenesis, especially when a transposon-based gene cassette is used. Based on this scenario, the transient expression of proteins by an in vitro-transcribed messenger RNA (IVT-mRNA) has become a subject of interest. The use of lipid nanoparticles (LNPs) for the transfection of IVT-mRNA is one of the more promising strategies for introducing exogenous genes. In this study, we report on the development of LNPs with transfection efficiencies that are comparable to that for electroporation in a T cell line (Jurkat cells). (2) Methods: Transfection efficiency was improved by optimizing the phospholipids and polyethylene glycol (PEG)-conjugated lipid components. (3) Results: Modification of the lipid composition resulted in the 221-fold increase in luciferase activity compared to a previously optimized formulation. Such a high transfection activity was due to the efficient uptake by clathrin/dynamin-dependent endocytosis and the relatively efficient escape into the cytoplasm at an early stage of endocytosis.